2012
DOI: 10.1007/s00216-012-6063-y
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separations of chiral polychlorinated biphenyls on three polysaccharide-type chiral stationary phases by supercritical fluid chromatography

Abstract: Enantiomeric separations of 18 chiral polychlorinated biphenyls (PCBs) were investigated on three polysaccharide-type chiral stationary phases (CSPs; Sino-Chiral OJ, Chiralpak IB, and Chiralcel OD) by supercritical fluid chromatography (SFC). With these commonly used polysaccharide CSPs, 17 PCBs except PCB 135 (R(S) = 0.81) were well resolved (R(S) > 1.5) under appropriate mobile phases and temperatures. Using Sino-Chiral OJ, 14 PCBs could be baseline-separated, while only one and nine PCBs could be completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this regard, chiral columns containing cellulose tris(4‐methylbenzoate) as chiral selectors furnished the best results. Lin and co‐workers reported the baseline enantioseparation of 17 chiral PCBs (Table ) using Sino‐Chiral OJ, Chiralcel OD, and Chiralpak IB (250 × 4.6 mm) as chiral columns by SCF . In this case, the preliminary screening was performed with a MP of 100% CO 2 at a FR of 2.0 mL/min and column temperature of 36°C.…”
Section: Liquid‐phase Enantioseparation Of Stable Atropisomersmentioning
confidence: 99%
“…In this regard, chiral columns containing cellulose tris(4‐methylbenzoate) as chiral selectors furnished the best results. Lin and co‐workers reported the baseline enantioseparation of 17 chiral PCBs (Table ) using Sino‐Chiral OJ, Chiralcel OD, and Chiralpak IB (250 × 4.6 mm) as chiral columns by SCF . In this case, the preliminary screening was performed with a MP of 100% CO 2 at a FR of 2.0 mL/min and column temperature of 36°C.…”
Section: Liquid‐phase Enantioseparation Of Stable Atropisomersmentioning
confidence: 99%
“…Previous works demonstrated that an increase in column temperature often causes short retention and worse resolution . To investigate the effect of column temperature on the resolution of sulfoxaflor stereoisomers, it was increased from 10 to 30ºC with 5ºC increments in this study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lin and colleagues reported the baseline enantioseparation of 17 out of 18 chiral PCBs (Table 13) using Sino-Chiral OJ, Chiralcel OD, and Chiralpak IB (250 × 4.6 mm) as chiral columns by SCF. 64 In this case, the preliminary screening was performed with a mobile phase of 100% CO 2 at a flow rate of 2.0 ml/min at a column temperature of 36°C. As reported in Table 14, some separations were optimized by adding alcoholic modifiers to the mobile phase.…”
Section: Polychlorinated Biphenyls and Derivativesmentioning
confidence: 99%